Peran Masjid dalam Menigkatkan Pendidikan Keagamaan Masyrakat Desa Brekat Tegal: Penelitian - Imam Tazali; Slamet Maryoso; Ery Suryani; Puspa Fortuna Zulfa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The results of this study indicate that the role of the mosque in improving the religious education of the Brekat Village Community is due to some people who use the mosque as a religious activity only. While the mosque has a role in all worship carried out by Muslims. Through qualitative methods, researchers have found that the role of the mosque is very influential in the religious education of the Brekat Tegal Village community. The role of the mosque makes the mosque a place of worship, religious activities, social activities and activities to gain knowledge for the Brekat village community.